Passive drag is still a good evaluator of swimming aptitude - Chatard, J. C.; Bourgoin, B.; Lacour, J. R. (European Journal of Applied Physiology, 1990)
Competitive swimmers (N = 218) were assessed for passive drag, performance level, anthropometry, and joint laxity (flexibility). Passive drag was measured at 1.4 m/s using a mechanical winch and strain gauge with a load cell connected to a strain bridge. Swimmers were towed in a prone position holding their breath after a maximal inspiration. Buoyancy was evaluated by hydrostatic lift, that is, the maximal weight just necessary to maintain the swimmer in a balanced position under the water after a maximal inspiration. Joint laxity was assessed normally. Passive drag was related mostly to surface area: r = .73 for males and r = .53 for females. For a given surface area, passive drag was inversely related to performance. Passive drag was influenced by joint flexibility. Hyperflexible Ss created less resistance because of the ability to streamline to a greater extent which contributes to more laminar flow and less turbulence around pressure (hard separation) points (shoulder, hip, knee, ankle). Surprisingly, hydrostatic lift was not found to be important although it increases and decreases with inspiration and expiration. After maximal expiration, the thoracic cross-section decreased between 10 and 20% while passive drag remained virtually constant. Thus, passive drag is primarily related to the pressure exerted by a swimmer's body on the water. Passive drag was also found to be lowest in elite swimmers. However, this investigation did not relate passive drag to active drag. One should not assume that passive is more important than active drag. Passive drag is a good indicator of general swimming aptitude. It may relate most to gliding phases in strokes. Implication: Passive drag can be reduced by increasing flexibility particularly of the shoulders. The thoracic cross-section area decreases on maximal expiration reducing "form resistance." Thus, it might be an advantage to expire maximally in the last five meters of a race to derive a very small benefit from the extra streamlining. A possible test for passive drag could be the "push and glide" with maximal inspiration. Since explosive leg strength is also included in that test it will confound results. However, swimmers who can glide further and longer should have a hydrodynamic advantage over those who cannot.